Pengaruh Brand Image dan Brand Awareness Terhadap Pembeli di Market Place (Studi Kasus pada Aplikasi Shopee) - Aisyah Fitri Pasaribu; Purnama Ramadani Silalahi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This journal aims to determine the effect of brand image and brand awareness on buyer decisions in the marketplace (a case study on the shopee application). The research method used by the author is a quantitative method by distributing questionnaires to respondents. The population of people who often shop online using the shopee application. Until the study, there were 75 people aged 18 to 30 years who often shopped at shopee. The test tool in this study used SPSS version 22